2013
DOI: 10.1108/jkm-12-2012-0394
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and managing knowledge loss

Abstract: Purpose – Research on knowledge loss is at an early stage of evolution. This paper seeks to extend the existent literature through an exploratory investigation of the drivers and impacts of knowledge loss, as well as associated retention strategies within manufacturing and service operations. Design/methodology/approach – Multiple research streams are used to explore and capture the complexities and intricacies of knowledge loss within four firms. The author follows a multiple case study approach with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
136
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(152 citation statements)
references
References 72 publications
6
136
0
10
Order By: Relevance
“…Many scientists emphasize that there is a lack of knowledge retention strategy in many organizations, since many executives of the organization focus only on the solutions provided by the information technology when preserving the knowledge while ignoring the importance of human factor (Daghfous et al 2013). The codification of the available knowledge and too wide utilization of IT shows very limited understanding of the nature of the available knowledge.…”
Section: Baporikar 2014mentioning
confidence: 99%
See 3 more Smart Citations
“…Many scientists emphasize that there is a lack of knowledge retention strategy in many organizations, since many executives of the organization focus only on the solutions provided by the information technology when preserving the knowledge while ignoring the importance of human factor (Daghfous et al 2013). The codification of the available knowledge and too wide utilization of IT shows very limited understanding of the nature of the available knowledge.…”
Section: Baporikar 2014mentioning
confidence: 99%
“…Intranet, internet, internal databases of the organisations, automated data transfer systems make many of the daily knowledge management processes easier, however only expressible knowledge can be retained in such way. After the individuals, who possess the tacit knowledge, leave such knowledge retention systems can suddenly lose the value (Daghfous et al 2013).…”
Section: Baporikar 2014mentioning
confidence: 99%
See 2 more Smart Citations
“…So every possible move has to be exercised to retain the key employees and their expertise if this becomes possible it will serve as an asset to the company [3] . The authors concluded in their study that knowledge work leads to better understanding of goals and apply better practices and create a sense of belongingness [4] . A study conducted by Boston consulting group speculated that in the USA and world-wide will be a shortage of about 60.5 million skilled workers by the year 2020 that will includes a shortage of knowledge workers of around 17 million in USA alone [5] .…”
Section: Introducionmentioning
confidence: 99%